Integrated Lean Warehousing Framework Reduces Lead Time in Raw Material Warehouse: Kerangka Kerja Lean Warehousing Terintegrasi untuk Mengurangi Lead Time pada Gudang Bahan Baku - M. Husin As Ari; Enny Aryanny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Warehousing process flow efficiency plays a crucial role in supporting manufacturing operational performance, yet warehouse activities are often dominated by non-value-added tasks. Specific Background: This condition was identified in the raw material warehouse of PT XYZ, a paint manufacturing company, where delays in material flow, repetitive administrative processes, and unstandardized verification procedures contributed to inefficiencies. Knowledge Gap: Although Lean Warehousing is widely recommended, studies integrating Value Stream Mapping (VSM), Process Activity Mapping (PAM), VALSAT, and Fishbone analysis in raw material warehouses remain limited. Aims: This study aims to identify dominant waste and formulate structured improvement proposals to improve warehouse flow efficiency. Results: Initial mapping identified 29 activities with a total lead time of 12,580.2 seconds and a Process Cycle Efficiency (PCE) of 11.70%, dominated by Necessary Non-Value-Added activities (9,811.6 seconds). After implementing the integrated Lean Warehousing framework supported by 5S principles, total lead time decreased to 10,944.8 seconds and PCE increased to 13.45%, representing a 1.75% improvement. Novelty: This research proposes a multi-tools integrated Lean Warehousing framework (VSM–PAM–VALSAT–Fishbone) specifically applied to a raw material warehouse in the paint industry. Implications: The findings demonstrate that structured waste identification and process simplification can systematically improve warehouse performance and provide a replicable model for manufacturing warehouse optimization. Highlights: Initial mapping revealed 29 activities dominated by Necessary Non-Value-Added time of 9,811.6 seconds. Process simplification reduced total flow duration from 12,580.2 to 10,944.8 seconds. Process Cycle Efficiency increased from 11.70% to 13.45% after structured improvement implementation. Keywords: Lean Warehousing, Process Activity Mapping, VALSAT, Value Stream Mapping, Fishbone Diagram